Poly(butylene adipate‐co‐terephthalate) (PBAT)/Antimony‐doped Tin Oxide Polymer Composite for Near Infrared Absorption Coating Applications. (14th May 2019) - Sim, Ju Yong; Raj, C. Justin; Yu, Kook Hyun
Abstract : The biodegradable poly(butylene adipate‐co‐terephthalate) (PBAT) polymer was synthesized via one pot synthesis technique using adipic acid and butanediol. The polymerization of synthesized sample was confirmed using FTIR, NMR, and TGA analysis. The PBAT/ATO films were fabricated via spray coating technique utilizing various concentrations of ATO nanoparticles in PBAT polymer solution and optimized the film quality through optical (NIR) and surface analysis. The polymer film having 7 wt % of ATO in PBAT showed good transparency in the UV, visible light and shown approximately 41% absorption in the near infrared region. Moreover, the 7 wt % ATO based polymer film exhibited low surface roughness and uniform coating over the substrate. In addition, near infrared absorbing efficiency of PBAT/ATO composite film in outdoor was demonstrated by constructing a PBAT/ATO (7 wt %)/vinyl greenhouse and the temperature differences were comparatively studied with a bare vinyl green house. Abstract : The biodegradable PBAT/ATO nano composite film showed potential towards near IR absorption coatings for outdoor applications.